PEMBUATAN BIODIESEL BIJI KARET DAN BIODIESEL SAWIT DENGAN INSTRUMEN ULTRASONIK SERTA KARAKTERISTIK CAMPURANNYA - Sabinazan musadhaz, Dwi Setyaningsih dan Djeni Hendra TIP (Jurnal Teknologi Industri Pertanian, 2012)
Biodiesel is one of known alternative fuels, obtained from vegetable oil, for example rubberseed oil and palm oil. Conventionally, biodiesel obtained by reacting oil with methanol and catalyst for one hour at temperature of 65 oC with mechanical stirring. Reaction time of this conventional method can be shortened by applying ultrasonic energy. The objectives of this research were to produce rubberseed biodiesel and palm biodiesel by applying ultrasonic energy, and to characterize palm biodiesel, rubberseed biodiesel, and blended of both. The result showed that ultrasonic transesterification of palm oil gave a greater yield than conventional methods, the yield ranged from 96.52% to 98.03% and the acid number ranged from 0.50 to 0.63 mg KOH/g sample for ultrasonic transesterification. Ultrasonic esterification succeeded in reducing acid value of rubber seed oil, which was smaller than acid value of 30 minutes by the conventional esterification. Ultrasonic transesterification only succeeded to produce biodiesel from rubberseed oil that has gone through the 30 minutes ultrasonic esterification (78.84% yield) and through an one hour conventional esterification (91.55% yield). Rubberseed biodiesel, oil palm biodiesel, and blended of both biodiesel met the SNI-04-7182-2006 on the characteristics of acid value, density, viscosity, and cloud point. The iodine number of rubberseed biodiesel was still above the standard, but adding oil palm biodiesel to rubberseed biodiesel can reduce the iodine number of blended biodiesel to met the standards.Keywords: biodiesel, rubberseed oil, palm oil, ultrasonic, blending characteristics